Analysis of the competitiveness of the cotton industry in Xinjiang based on the diamond model - Lei Wang; Benfu Lv (UTMS Journal of Economics, 2021)
This paper uses the diamond model theory as the basic research perspective to explore how the upstream and downstream industrial chains of cotton in Xinjiang can escape from the constraints of reality and how their resource endowments can be transformed into competitive advantages. This paper compares and analyzes the domestic and foreign cotton-producing regions and their related cotton products import and export situation and it also uses Potter's diamond theory. It takes six factors as the core of study which includes production factors, demand conditions, related and supporting industries, the strategic structure of enterprise and competitors, government, opportunities to analyze the problems and short-coming of current development of the cotton industry in Xinjiang. It also tries to find a way to achieve leap-forward development of the cotton industry in Xinjiang. How to add value and empower raw material primary products such as cotton, and how regions can base on local resource endowment, play a good resource advantage and enhance the competitiveness of advantageous industries.
Keywords: 330; diamond theory; cotton; resources; competitiveness; industrial development